2013
DOI: 10.1111/ijfs.12274
|View full text |Cite
|
Sign up to set email alerts
|

Study of different fouling mechanisms during membrane clarification of red plum juice

Abstract: Summary In this study, the flux decline mechanisms were identified during membrane clarification of red plum juice at several processing parameters, including pore size, membrane type, transmembrane pressure, temperature and velocity. The results were used to investigate the effect of changes in operating conditions on the intensity of membrane fouling. Also, scanning electron microscopy (SEM) was used for analysing fouling‐layer morphology. These results showed that the main mechanism responsible for membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Again pure water flux of cleaned membrane (Jw) was calculated. The fouling factor ( F ) of membrane can be calculated using the following equations (Cassano et al ., ; Juang et al ., ; Nourbakhsh et al ., ,b): Jnormalw=QA.ΔTJnormalw=ΔPnormalμnormalwRR=Rm+Rf%F=JwJwJnormalw×100…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Again pure water flux of cleaned membrane (Jw) was calculated. The fouling factor ( F ) of membrane can be calculated using the following equations (Cassano et al ., ; Juang et al ., ; Nourbakhsh et al ., ,b): Jnormalw=QA.ΔTJnormalw=ΔPnormalμnormalwRR=Rm+Rf%F=JwJwJnormalw×100…”
Section: Resultsmentioning
confidence: 96%
“…The variation in ω3‐PUFA concentration due to change in stirring rate can be related to the fouling factor. To calculate the fouling created due to oil transport in ETNA01PP, the pure water flux ( J w ) through membrane was calculated according to eqn , and by equalling the eqns and , the membrane resistance was calculated (Cassano et al ., ; Juang et al ., ; Nourbakhsh et al ., ,b). Jnormalw=QA.ΔTJnormalw=ΔPnormalμnormalwRnormalm, where J w is the pure water flux (L m −2 h), Q is the quantity of the water permeate (L), A is the membrane area (m 2 ), Δt is the sampling time (h), ΔP is feed pressure (Pa), μ w is water viscosity (Pa.s), and R m is membrane resistance.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, the permeate flux increases with a rise in the feed temperature (Nourbakhsh et al ., ). Evaluation of the feed temperature during the microfiltration of the pomegranate juice in an ultrasonic bath showed that the temperature increases from 30 to 50 °C during the membrane process.…”
Section: Resultsmentioning
confidence: 97%
“…Aggregates of whey proteins and polysaccharides from orange, such as lignin, cellulose, and pectin may cause permeate flux decline (Nourbakhsh et al, 2014). While most academic studies have focused on enzymatic treatments to improve filterability of fruit juices, this research followed the trend of minimally processed foods, excluding the enzymatic treatment of orange juice in order to minimize industrial costs.…”
Section: Juice Into a Micro-filtered Beveragementioning
confidence: 99%